The association between vegetarian diet and varicose veins might be more prominent in men than in women - Tsai, Cheng-Ken; Nfor, Oswald Ndi; Tantoh, Disline Manli; Lu, Wen-Yu; Liaw, Yung-Po (Frontiers in Nutrition, 2023)
Background: Varicose veins (VVs), a common vascular disease is associated with a huge medical burden. The prevalence in women surpasses that in men. The role of vegetarian diets in the pathogenesis of the disease remains inconclusive. In this study, we examined the risk of VVs in vegetarian and non-vegetarian men and women. Methods: The study involved 11,011 adults whose data were obtained from Taiwan Biobank between 2008 and 2020. Information on VVs, sex, and vegetarian diets was obtained from participants’ self-responses to the Taiwan Biobank questionnaires. Results: The study subjects consisted of 4,142 men and 5763 women. About 12 % of men and 35 % of women had VVs. Study participants were predominantly non-vegetarians (91.84 % were men and 88.24 % were women). Women had a higher risk of VVs than men. The odds ratio (OR); 95 % confidence interval (CI) was 3.414; 2.995-3.891. There was a significant interaction between sex and vegetarian diets (P = 0.0034). Women were at higher risk of VVs than men both in the vegetarian (OR = 1.877, 95 % CI = 1.270-2.774) and non-vegetarian (OR = 3.674, 95 % CI = 3.197-4.223) groups. Based on vegetarian diets, only vegetarian men had a higher risk of VVs (OR = 1.453, 95 % CI = 1.069 to 1.976). Based on the sex-stratified model, the risk of VVs was significantly higher in vegetarian men (OR = 1.457, 95 % CI = 1.072-1.979), and in vegetarian and non-vegetarian women with corresponding ORs (95% CI) of 3.101 (2.528- 3.803) and 3.599 (3.140-4.124), respectively. Conclusion: Women were more susceptible to varicose veins compared to men, regardless of diet. However, in terms of diet, only men who followed a vegetarian diet were at greater risk for developing VVs.